Étude et analyses des dégradations du manuscrit de Nizet - Cecilia Duminuco (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The Nizet manuscript of the 18th century covers the genealogy of four families of Verviers : the Nizet, Graffard, Hacraÿ and Laurentÿ families. The book is damaged and presents black stained areas in the paper which are transfers of gold-like and silver-like painted decorations. The purpose was to achieve a better understanding of the materials and degradations of the manuscript.